Implementation of Integrated Reporting in Several Asian Countries - Halimah Setiaji; Novia Putri (Journal of Comprehensive Science, 2026)
Integrated Reporting (IR) is a reporting approach that combines financial and non-financial information into a single report to demonstrate a company's ability to create sustainable value. The adoption of IR has gained increasing attention from regulators, practitioners, and academics worldwide, including in Asia. Although Indonesia has not yet mandated the widespread implementation of IR, several companies have begun adopting this framework. Across Asia, the development of IR implementation varies, with many countries facing challenges in integrating non-financial performance and meeting stakeholder expectations. This study aims to provide an overview of the development of IR implementation in several Asian countries, as well as to identify the challenges and benefits faced by companies in the implementation process. The research employs a qualitative descriptive method with a literature study approach, collecting secondary data from academic journals, articles, and books related to IR adoption in Asia. The findings reveal that IR implementation in Asia remains limited, with varying levels of adoption across countries such as Indonesia, Malaysia, Korea, Japan, Thailand, and Armenia. Key challenges include difficulties in measuring non-financial information, lack of expertise, low corporate awareness, and high preparation costs. Despite these obstacles, companies that have adopted IR report benefits such as improved reporting quality, enhanced stakeholder trust, and better alignment with sustainable development goals. This study concludes that while IR adoption in Asia is still developing, increasing awareness and regulatory support could accelerate its implementation.